Effects of Multidimensional Self-Esteems on Health Promotion Behaviors in Adolescents - Liu, Bin; Tian, Lu; Yang, Shuo; Wang, XueQiang; Luo, Jiong (Frontiers in Public Health, 2022)
Objective: To explore the relationship among adolescents' socio-economic background factors, multidimensional self-esteem and health promotion behavior, so as to provide an important reference for the intervention of health promotion behavior and self-esteem education in the future. Methods: Taking adolescents in Chongqing as the object, the students of 10 health promotion schools were investigated by zonal random sampling, and spss21 0 and amos19 0 two statistical analysis software are used to process the obtained database. Results: 1) gender and age significantly affected adolescents' self-esteem and health promotion behavior ，which showed that Men's perception of self-esteem was lower than that of women, while girls were more likely to implement health promotion behavior than boys; 2) Children from two parent families or families with higher parental education are more able to implement health promotion behavior and enjoy higher self-esteem, while family economic status has no effect on adolescents' self-esteem and health promotion behavior; 3) Compared with students in ordinary schools, adolescents in health promotion schools（HPS）have higher self-esteem and can implement health promotion behavior more; 4) The higher the self-esteem of adolescents, the better their health promotion behavior; The higher the sense of interpersonal ability, the more able to implement social support behavior; The higher the sense of physical ability and physiological value, the more able to implement sports behavior; The higher the sense of academic ability, the more able to implement nutritional behavior; The higher the external recognition and physiological value, the better the performance of nutritional behavior and stress management; The higher the internal evaluation, the more able to implement health responsibility and exercise behavior. Conclusion: Socio-economic background can indeed have a direct or indirect impact on adolescent health promotion behavior, and multidirectional self-esteem can explain about 70% of the variation of health promotion behavior, which seems to suggest that improving adolescent self-esteem is the focus of health promotion and health education in the future.